2013
DOI: 10.3109/08923973.2013.770521
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity, analgesic and anti-inflammatory activities of tectorigenin

Abstract: We demonstrated that tectorigenin is a safe and promising analgesic and anti-inflammatory agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…[ 25 ] As for tectorigenin, previous research found that the median lethal dose of tectorigenin on mice was 1.78 g/kg. [ 12 ] The research also demonstrated that tectorigenin showed no toxicity to mice at a high dose of 300 mg/kg. However, the toxicity of tectorigenin has not been studied in guinea pigs yet.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…[ 25 ] As for tectorigenin, previous research found that the median lethal dose of tectorigenin on mice was 1.78 g/kg. [ 12 ] The research also demonstrated that tectorigenin showed no toxicity to mice at a high dose of 300 mg/kg. However, the toxicity of tectorigenin has not been studied in guinea pigs yet.…”
Section: Discussionmentioning
confidence: 98%
“…Belamcanda chinensis is a traditional Chinese medicine, which has been used to treat cough and pharyngitis in many Eastern countries. [ 12 ] Tectorigenin is a main component of B. chinensis , and it is a methoxylated isoflavone with various biological activities, including antioxidation, hepatoprotection and anti‐inflammation. [ 13,14 ] The anti‐inflammatory effect of tectorigenin has been investigated and reported in several researches.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of being a more appropriate assay for opioids, this acetic acid-induced writhing test is widely used as a model of induction of inflammatory origin pain, as the acetic acid solution induces the synthesis of arachidonic acid metabolites and other inflammation mediators (Ha et al, 2013). Thus, the antinociceptive effects of non-steroidal anti-inflammatories and peripheral analgesics may also be observed from this model.…”
Section: Discussionmentioning
confidence: 99%
“…( Furusawa et al, 2009 ; Zhu et al, 2019 ). In addition, tectorigenin which is an effective component derived from Belamcanda chinensis, has attracted considerable interest because of its anti-inflammatory activity ( Ha le et al, 2013 ; Pan et al, 2008 ). However, their targets for anti-inflammatory activity were not clear.…”
Section: Discussionmentioning
confidence: 99%